Critical success factors and challenges for product development: a case study approach - Liew, Cindy (2022)
Project failures in new product development (NPD) are common, and they usually happen near the conclusion of the development process or later in the commercialization stage. The market is always hungry for new products and services as technology and consumer purchasing power improve. Projects for new product development (NPD) frequently fail, either at the end of development or later in the commercial stage. The root causes of failure are frequently linked back to NPD's early phases, sometimes known as the front end. The goal is to look into the important success criteria for product development, as well as predicted problems, and to provide a resource for product development companies. What variables contribute to a successful product development? Identifying these characteristics can save you money in the long run. When comparing the two sets of data, three things stand out: cross-functional collaboration, the implementation of a structured NPD process, and a focus on innovation and out-of-the-box thinking. This research has mostly focused on the corporate aspects that influence the success of new product development. It discussed what companies can do internally, but it didn't say much about what they can do with external elements to improve their success rate. It is suggested that you concentrate on external elements and problems when developing a product. It's crucial to emphasise that, depending on their business nature, product kind, top management strategies, and culture, different firms require a distinct combination of CSFs. Furthermore, it is feasible to discover that some CSFs are more important at certain stages of the NPD process.